A comparative study between the adapted and original READS among the students of the Saudi Arabia - Masoud Alotaibi, Nasser; Abdul Malik Mohamed Ismail, Shaik (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the current study is to develop and profile a comparison within the adapted and original READS among the students of English in Saudi Arabia. For this purpose, the data was collected from the 100 EFL students who were studying in the universities of Saudi Arabia. “The mixed-methods approach was employed, which consists of both the qualitative and quantitative approaches. The key findings have shown that the value of original READS is less than 0.50, which is to consider the original READS correctness insufficient. Moreover, the second question of the study was achieved through the item objective congruence analysis. The value was 0.88, which was high from the assumed value, which is 0.50. Therefore, the value of adapted READS showed suitability according to the Saudi environment. In addition, the third research question was achieved by using the descriptive analysis as compared in both the original and adapted READS. The key findings have shown that adapted READS have good results as compared to the original READS. The fourth research question of the study was to be achieved by using a paired sample test (T-Test). Fundamentally, a comparison was performed with the results of the original and the adapted READS in the students of Saudi Arabia universities. The key findings have shown that there are statistically significant differences existing in the respondent's performance of the adapted READS test as opposed to the original READS version. Thus, these findings have shown that there is a difference between the adapted READS and the original READS in university students of Saudi Arabia.”